Study of RCC Silo structure for different Height/Dia. ratio. - Nighute, Avinash; V. R., Rathi (Proteus, 2022)
This work shows the effect of height to diameter ratio on reinforced cement concrete circular silo. Janssen's theory as per IS 4995:1974 part I & part II is used to determine the load intensity and structural dimensions. The Response Spectrum Method along with Wind load Analysis is used for analysis of the reinforced cement concrete silo structures. In the present studies, the silo structures are considered to be in Zone V of IS 1893:2005 Part 3 and IS 875:2015 Part IV. SAP 2000 software is used for the modelling and analysis of silo structure. Two different heights to diameter ratios are used for getting results on four models in the form of horizontal pressure on the silo wall due to stored material, displacement and base shear. The displacement will be more at the top of the structure due to increase in height of the silo. For earthquake and wind load analysis, empty silo structure shows the maximum value of displacement and base shear.